Phase-separating peptide coacervates with programmable material properties for universal intracellular delivery of macromolecules - Sun, Yue (2025)
Phase-separating peptides (PSPs) self-assembling into coacervate microdroplets (CMs) are a promising class of intracellular delivery vehicles that can release macromolecular modalities deployed in a wide range of therapeutic treatments. However, the molecular grammar governing intracellular uptake and release kinetics of CMs remains elusive. Here, we systematically manipulate the sequence of PSPs to unravel the relationships between their molecular structure, the physical properties of the resulting CMs, and their delivery efficacy. We show that a few amino acid alterations are sufficient to modulate the viscoelastic properties of CMs towards either a gel-like or a liquid-like state as well as their binding interaction with cellular membranes, collectively enabling to tune the kinetics of intracellular cargo release. We also demonstrate that the optimized PSPs CMs display excellent transfection efficiency in hard-to-transfect cells such as primary fibroblasts and immune cells. Our findings provide molecular guidelines to precisely program the material properties of PSP CMs and achieve tunable cellular uptake and release kinetics depending on the cargo modality, with broad implications for therapeutic applications such as protein, gene, and immune cell therapies.